Epidemiological profile of patients with cleft lip and palate in a reference service in the Federal District - Eduarda Vidal Rollemberg; Tayane Oliveira Pires; Gabriela Nascimento Moraes; Liliane Rodrigues Rios; Luciano Gazzoni Machado; Marconi Delmiro da-Silva; Diderot Rodrigues Parreira (Revista Brasileira de Cirurgia Plástica, 2019)
Introduction: Cleft lip and palate, the most common congenital malformations of the head and neck, result from fusion failure of embryonic facial processes during the first 12 weeks of pregnancy. Their phenotypic presentation varies and involves different levels of complexity. The objective is to determine the epidemiological profile of patients with cleft lip and palate treated at the Hospital Regional da Asa Norte regarding sex, cleft type, laterality, age, presence of associated syndromes, and corrective surgical procedures. Methods: This was a retrospective descriptive study of 322 medical records of patients treated by the HRAN team from August 2013 to July 2017. The data collected were entered into an Excel spreadsheet and submitted to statistical analysis. The study received ethical approval. Results: Of the 322 patients enrolled in the service, 169 were male (52.48%). The most frequent type of cleft was the trans-foramen (65.25%). With regard to laterality, a higher prevalence of cleft was observed on the left (20.50%). Only 19% of the patients had associated malformations. Cheiloplasty was the most frequent surgical correction performed by service (54%). The age of the patients was 1-53 years (median, 1.87 years). Conclusion: The study contributes information important to society, government, and treatment professionals. In line with the literature, the more prevalent cleft was unilateral left trans-foramen and the most frequent surgery was cheiloplasty.